What happened to the fig tree? An empirical study in psychological type and biblical hermeneutics - Francis, Leslie J. (Mental health, religion & culture, 2012)
The SIFT method of biblical hermeneutics and liturgical preaching has its roots in Jungian psychological type theory and maintains that the reading and interpretation of text is shaped by individual preferences within the perceiving process (sensing and intuition) and within the evaluating process (thinking and feeling). The present study tests the empirical foundation for this method by examining the way in which three groups of participants familiar with handling scripture (N = 31, 14, and 47) interpret the Marcan narrative concerning the cleansing of the temple and the cursing of the fig tree. The data provide further support for the psychological principles underpinning the SIFT method.